Flow channel dimensional accuracy of bipolat plate fabrication through milling machining process - Selamat, Mohd Zulkefli; Hamdan, Hamzaitul Akmarizal; Ali, Mohd Basri; Dhar Malingam, Sivakumar (Penerbit UTeM Press, 2022)
This book basically aimed on the advanced approach for future technology in science. engineering and technology. Based on this book, it will help readers for gain more understanding and knowledge for applying a knowledge either as a solution provider for future technology, or as a solver for human issues for new challenging, respectively. Last but not least, this book covered the advanced solution starting from for human problem capacity in workplace until the new technology for nanotechnology.